The Use of Electronic Guessing Games to Increase Vocabulary Mastery - Fitrotul Mufaridah; Nurkamilah; Aminullah, Anggi Aminullah (English Education Program, Education Faculty, Universitas Nurul Huda, 2023)
Learning English as an international language may have generated an issue with vocabulary problems recognizing aspects during its process which the learning process lives of students cannot be overstated. The objective of this research is to refer to the research problem to find out how electronic guessing games increase vocabulary mastery. The hypothesis of this research is described as follows: applying electronic guessing games at MTs Nurul Hasan Bondowoso in the 2022/2023 academic years and focusing on increasing students' English language, especially vocabulary mastery. The design of this research is classroom action research. the research is VII A class consisting of 15 students. The data are collected using the test method by the Quizizz platform and the instrument used is test items with a covering of classification vocabulary. Electronic guessing games were able to increase the student’s vocabulary mastery according to the criteria of success at MTs Nurul Hasan Bondowoso in the 2022/2023 academic years by student’s ability to use technology, with technical fluency in using technology, it was easier for students to connected the picture to clues to find out the right answer.